IMPLEMENTATION OF DHT11 SENSOR AND YL-69 SENSOR IN AUTOMATIC PLANT WATERING SYSTEM BASED ON INTERNET OF THINGS (IOT) USING BLYNK - Auliany, Shylvia Rizki; Dani, Ahmad; Tarigan, Amani Darma (STABN RADEN WIJAYA WONOGIRI, 2024)
Naturally, plants need water and nutrients that are essential for their growth and development. Therefore, watering the plant must be done regularly every day to keep the plant healthy. If watering is not done in accordance with the required time, the plant will have difficulties in the process of photosynthesis and food production, which can be fatal, including the death of the plant or disruption of its growth process. Many people have difficulty watering plants at the right time due to busyness or ignorance. To solve this problem, an automatic watering system is needed that can be set according to the schedule and allows remote control using a microcontroller. In this study, several components were used, such as the RTC DS3231 to access the time accurately, the YL-69 sensor to detect soil moisture so that if the soil is already moist enough the system will not water. DHT11 to measure the temperature and humidity of the surrounding air, if the soil condition is dry but the temperature is too hot, watering will not be carried out because it can damage the plant. Relays are used to control water pumps. All of these components are integrated in an ESP32 NodeMCU. The system will run water pumps every 8:00 a.m. and 4:00 p.m. every day. The test results concluded that the system can work well where this system has the ability to increase efficiency and productivity in the process of watering plants.